2015
DOI: 10.1186/s12879-015-0781-7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment efficacy, treatment failures and selection of macrolide resistance in patients with high load of Mycoplasma genitalium during treatment of male urethritis with josamycin

Abstract: BackgroundAzithromycin has been widely used for Mycoplasma genitalium treatment internationally. However, the eradication efficacy has substantially declined recent decade. In Russia, josamycin (another macrolide) is the recommended first-line treatment for M. genitalium infections, however, no data regarding treatment efficacy with josamycin and resistance in M. genitalium infections have been internationally published. We examined the M. genitalium prevalence in males attending an STI clinic in Moscow, Russi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 39 publications
3
57
0
9
Order By: Relevance
“…Another macrolide, josamycin, is widely used in Russia for treatment of M. genitalium ‐positive patients as first‐line treatment. In a recently published study, josamycin given as 500 mg three times a day for 10 days showed a 93.5% eradication rate in males with urethritis caused by macrolide‐susceptible M. genitalium . Macrolide resistance to this 16‐membered macrolide was reported with approximately the same rate as for azithromycin but the mutation was selected at the A2062G position of the 23S rRNA gene (different from the A2058G/A2059G mutations described for azithromycin).…”
Section: Therapymentioning
confidence: 96%
“…Another macrolide, josamycin, is widely used in Russia for treatment of M. genitalium ‐positive patients as first‐line treatment. In a recently published study, josamycin given as 500 mg three times a day for 10 days showed a 93.5% eradication rate in males with urethritis caused by macrolide‐susceptible M. genitalium . Macrolide resistance to this 16‐membered macrolide was reported with approximately the same rate as for azithromycin but the mutation was selected at the A2062G position of the 23S rRNA gene (different from the A2058G/A2059G mutations described for azithromycin).…”
Section: Therapymentioning
confidence: 96%
“…Jensen et al found mutations in region V of the 23S rRNA gene in positions 2058 and 2059 ( Escherichia coli numbering) accounting for some of the macrolide failures seen [15]. High bacterial load may also be associated with treatment failure [16, 17]. In cases of treatment failure moxifloxacin, a fluoroquinolone, is recommended as a second line treatment [7].…”
Section: Introductionmentioning
confidence: 99%
“…Высокую эффективность в лечения МгИ пока-зало использование джозамицина по схеме 500 мг 3 раза в сутки в течение 10 дней, что позволило до-стичь эффективности лечения в 93,5% [46]. Джоза-мицин включен в качестве альтернативного препа-рата для лечения хламидийной инфекции в Реко-мендации IUSTI/ВОЗ и в качестве одного из основ-ных препаратов в рекомендациях РОДВиК 2012 г.…”
Section: клиническая дерматология и венерология 3 2015unclassified